Theory and Applications of Applied Electromagnetics APPEIC 2015 - Soh, Ping Jack.; Sulaiman, Hamzah Asyrani; Othman, Mohd Azlishah; Abd. Aziz, Mohamad Zoinol Abidin; Abd Malek, Mohd Fareq; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
In this book, experts from academia and industry present the latest advances in scientific theory relating to applied electromagnetics and examine current and emerging applications particularly within the fields of electronics, communications, and computer technology. The book is based on presentations delivered at APPEIC 2015, the 2nd Applied Electromagnetic International Conference, held in Krabi, Thailand in December 2015. The conference provided an ideal platform for researchers and specialists to deliver both theoretically and practically oriented contributions on a wide range of topics relevant to the theme of nurturing applied electromagnetics for human technology. Many novel aspects were addressed, and the contributions selected for this book highlight the relevance of advances in applied electromagnetics to a variety of industrial engineering problems and identify exciting future directions for research.
Keywords: Telecommunication; Computational intelligence; Computer networks .; Electronics; Industrial engineering; Production engineering; Microwaves, RF Engineering and Optical Communications; Computational Intelligence; Computer Communication Networks; Electronics and Microelectronics, Instrumentation; Industrial and Production Engineering